Preparation method and application of single-walled carbon nanotube conductive paste
The chemical vapor deposition method of the modified furnace body synthesized high-purity single-wall carbon nanotube conductive paste was solved, and the problems of medium yield and low purity in the prior art were achieved, efficient electron and ion transmission of lithium ion batteries were achieved, and the electrochemical performance of lithium iron phosphate was optimized.
Patent Information
- Application Number
- CN202510578594.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2025-08-05
AI Technical Summary
The synthesis method of single-wall carbon nanotubes in the prior art has low yield and purity, which leads to poor electron and ion transmission efficiency in the positive electrode materials of lithium-ion batteries, making it difficult to optimize the electrochemical performance of lithium iron phosphate.
Using the chemical vapor deposition method of the modified furnace body, high-purity single-wall carbon nanotubes were synthesized through catalytic ferrocene and sublimated sulfur, and impurities were removed by hydrochloric acid purification treatment to prepare a highly conductive single-wall carbon nanotube conductive paste, which was applied to lithium iron phosphate positive electrode material.
The yield and purity of single-wall carbon nanotubes are improved, and a continuous and stable conductive network is built, which significantly improves the first charge and discharge efficiency of lithium-ion batteries and the discharge specific capacity under high current density, reduces internal resistance, and optimizes the conductive performance of lithium iron phosphate.
Smart Images

Figure CN120432236A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive pastes, in particular to a preparation method of single-walled carbon nanotube conductive paste and application thereof. Background Art
[0002] The world is currently facing a crisis of non-renewable energy and significant environmental pollution. The development and utilization of electricity from renewable energy sources is particularly pressing. Lithium-ion batteries, due to their high energy density, reversibility, and lack of memory effect, have become the preferred choice for multifunctional electronic energy storage devices and new energy vehicles. While technological advancements have yielded significant success in new energy vehicles, lithium-ion batteries also face pressing challenges. For example, while ternary cathode materials offer excellent conductivity, they pose significant safety risks. While they offer high energy density and long battery life, they are prone to ignition, while lithium iron phosphate (LiFePO4) offers greater stability. Secondly, and currently a major challenge internationally, resource allocation is constrained. Ternary cathode materials contain precious metals such as cobalt, resulting in high costs. LiFePO4's lower cost makes it more competitive in the market. Consequently, LiFePO4 is replacing ternary cathode materials. However, LiFePO4 itself suffers from low energy density and poor conductivity. To address these shortcomings, researchers have found that using conductive additives with higher conductivity is one of the most effective methods. However, common Super-P, carbon black, graphene and multi-walled carbon nanotubes (CNTs) on the market still cannot meet the requirements. Therefore, it is urgent to find a carbon-based conductive agent with higher conductivity.
[0003] Single-walled carbon nanotubes (SWNTs) have a high degree of graphitization, crystallinity and ultra-high aspect ratio and show performance far superior to ordinary conductive agents in LiFePO4 positive electrodes. SWNTs are composed of carbon atoms in the form of sp 2 The hexagonal cylindrical surface formed by the complete bonding of hybridization and surrounding atoms can also be understood as a curled-up layer of graphene sheets.
[0004] Currently, the main methods for synthesizing SWNTs include arc discharge, laser etching, solid-phase pyrolysis, and flame synthesis. Typically, these synthesized SWNTs have low yield and purity and high energy consumption, which hinders the transport of electrons and ions in LiFePO4 applications. To address the shortcomings of existing SWNTs, such as low purity and yield, and the need for LiFePO4 cathode materials with optimized electrochemical performance, the present invention provides a method for the high-purity, continuous, and controllable growth of SWNTs and their conductive slurry. Summary of the Invention
[0005] The present invention aims to improve the purity and yield of SWNTs and optimize the electrochemical performance of LiFePO4 cathode materials by addressing the problems existing in the current synthesis technology of SWNTs and their conductive pastes, as well as their practical application in lithium-ion battery cathode materials.
[0006] The present invention aims to provide a method for preparing a single-walled carbon nanotube conductive paste, comprising the following steps: Step 1, weigh a certain amount of ferrocene and sublimed sulfur, mix and grind them evenly in a mortar; Step 2, placing the ferrocene containing sulfur or sulfur-substituted organic matter in step 1 in a preheating area; Step 3: Heat the reaction zone to above 1000°C, and after the temperature stabilizes, heat the preheating zone in step 2 to above 200°C; Step 4: After the temperature stabilizes, a certain amount of methane, hydrogen and inert gas are introduced and the sulfur-containing ferrocene vaporized in step 3 is carried into the high-temperature reaction zone; Step 5: Using chemical vapor deposition to in-situ reduce and catalytically crack to synthesize high-purity and high-conductivity single-walled carbon nanotubes; Step 6: purifying the single-walled carbon nanotubes synthesized in step 5 with hydrochloric acid to remove iron particles in the single-walled carbon nanotubes; Step 7: Weigh a certain amount of the single-walled carbon nanotubes treated in the previous step and mix them with NMP, PVP and PVDF solutions in proportion, and disperse them into a stable and uniform single-walled carbon nanotube conductive slurry through ultrasonic vibration and magnetic stirring.
[0007] Preferably, the molar ratio of ferrocene to sublimed sulfur is 8-32:1, and the sublimed sulfur is a sulfur-containing thio-organic compound.
[0008] Preferably, the preheating zone is required not to be affected by the temperature of the high-temperature reaction zone by modifying the equipment, that is, when the reaction zone reaches above 1000°C, the temperature of the preheating zone is still below 100°C.
[0009] Preferably, the temperature of the preheating zone is 120-220°C.
[0010] Preferably, the preheating zone and the high-temperature reaction zone are protected by inert gases Ar2 and N2 throughout the entire process until the reaction is completed and the temperature drops to room temperature.
[0011] Preferably, the flow rate of hydrogen and methane is 1-2:1, the flow rate of argon to hydrogen and methane is 2:1, and the inert gas and hydrocarbons carry the vaporized sulfur-containing ferrocene. It should be noted that the gas flow rate should not be too large to avoid incomplete reaction between the catalyst and the carbon source and tail end blockage; in situ catalytic cracking requires the simultaneous introduction of a certain amount of hydrocarbons.
[0012] Preferably, the hydrochloric acid purification treatment is to dilute 99.9% concentrated hydrochloric acid to 0.4 mol / L, heat to 80° C. and stir for 6 h, then filter and wash until neutral, and repeat 2-3 times.
[0013] Preferably, the addition amount of single-walled carbon nanotubes in the single-walled carbon nanotube conductive slurry is 2-0.5%, PVP:SWNTs=1:5; the maximum power of the ultrasonic power is 650W, the ultrasonic frequency is 40KHz, the ultrasonic oscillation time is 40-90min, the magnetic stirring voltage is 220V / 50Hz, the initial stirring time is 10-15h, the stirring time after the start of ultrasound is 40-90min, and the ultrasound and stirring are alternately cycled 5-8 times.
[0014] Preferably, the NMP is N-methylpyrrolidone, and its content is 94-96%.
[0015] The present invention also provides an application of a single-walled carbon nanotube conductive slurry. The prepared single-walled carbon nanotube conductive slurry is suitable for the production of all lithium iron phosphate battery positive electrode materials.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention realizes the reaction conditions for synthesizing SWNTs using ferrocene as a catalyst by simply modifying the existing furnace body, ultimately producing high-purity SWNTs and effectively improving their yield.
[0017] 2. The SWNTs synthesized in the present invention have a higher aspect ratio and crystallinity than Super-P and CNTs. When applied to LiFePO4, they can effectively connect positive electrode particles of uneven sizes and build a continuous and stable conductive network.
[0018] 3. After the SWNTs conductive paste prepared by the present invention is applied to LiFePO4 and assembled into a lithium-ion battery, its initial charge and discharge efficiency is significantly improved, the internal resistance is effectively reduced, and it still has excellent discharge specific capacity at high current density.
[0019] 4. The SWNWTs synthesized in the present invention significantly improve the problems of low energy density and poor conductivity of LiFePO4, and significantly optimize its conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 TEM image of the single-walled carbon nanotube of the present invention; Figure 2 is the Raman curve of the single-walled carbon nanotube of the present invention; Figure 3 This is an SEM image of the single-walled carbon nanotube conductive paste of the present invention applied to a LiFePO4 positive electrode sheet; Figure 4This is a schematic diagram of the furnace body modified according to the present invention; In the figure: 1. Preheating zone, 2. High-temperature reaction zone No. 1 (400-500℃), 3. High-temperature reaction zone No. 2 (700-800℃), 4. High-temperature reaction zone No. 3 (above 1000℃), 5. High-temperature reaction zone No. 1 (700-800℃), 6. Tail end gas outlet area, 7-9. Methane, hydrogen and argon gas inlets, 10. Alumina insulation pipe plug with a diameter of 87*66mm.
[0021] Figure 5 The first charge-discharge curve and efficiency of the single-walled carbon nanotube conductive paste of the present invention applied to lithium-ion batteries; Figure 6 The rate curve of the single-walled carbon nanotube conductive paste of the present invention applied to lithium-ion batteries; Figure 7 This is the internal resistance curve of the single-walled carbon nanotube conductive paste of the present invention applied to a lithium-ion battery. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Example
[0023] First, weigh a certain amount of ferrocene and sublimed sulfur in a molar ratio of 16:1, place them in an agate mortar and grind for more than 20 minutes to mix them evenly, and then place them in the preheating area; before that, in order to prevent the temperature of the high-temperature reaction zone from affecting the preheating zone, it is necessary to add an alumina pipe plug for heat insulation, and the diameter of the pipe plug should not be close to the inner diameter of the quartz tube, so that the gas phase catalyst can flow into the reaction zone to prevent blockage. After the pipeline is connected, argon is introduced at 1L / min for 10 minutes to clean the gas path and exhaust the air, and then the temperature of temperature control zone No. 3 is raised to 1000℃, and the temperature of temperature control zone No. 3 is stabilized to 1000℃; the temperature of temperature control zones No. 2 and 4 is stabilized at 800℃, and the temperature fluctuation does not exceed 30℃; temperature control zone No. 1 is stabilized to 500℃, and the temperature fluctuation does not exceed 30℃. Figure 4 At this point, the preheating zone temperature was raised to 200°C. Once the preheating zone temperature exceeded 110-120°C, methane was introduced at 50 ml / min, followed by hydrogen at 100 ml / min. Argon was then increased to 300 ml / min. The reaction was continued for 20 minutes. Under the protection of argon, the temperature was lowered to room temperature. The product was scraped off and recorded as hetero-SWNTs. 500 ml of 0.4 mol / L hydrochloric acid solution was prepared and stirred at 80°C for at least 8 hours for the hetero-SWNTs. This was repeated 2-3 times to obtain the purified product, recorded as SWNTs. Figure 1The TEM images of the synthesized SWNTs can be clearly seen, and their diameters are between 1.5 and 1.9 nm; Figure 2 The Raman image of SWNTs shows that the synthesized SWNTs have a strong RBM peak and a very low D peak intensity. The IG / ID value is as high as 8.85, indicating a very high degree of graphitization.
[0024] Weigh 0.05g of the dispersant PVP and 0.08g of the binder PVDF and dissolve them in 1.8g of N-methylpyrrolidone with stirring for 4-6 hours. Once the solution is clear and the bubbles disappear, add 0.04g of SWNTs and stir for 1 hour. Then, ultrasonicate for 1 hour. Repeat this process 7-9 times. Because the excellent structural properties of single-walled carbon nanotubes result in high van der Waals forces, which can cause agglomeration, a higher number of repetitions is necessary. Ultimately, the SWNTs are evenly dispersed in the NMP solution to produce a SWNT conductive slurry.
[0025] 1.88g of LiFePO4 positive electrode material was weighed and SWNTs conductive slurry was added, wherein the mass ratio of LiFePO4, PVDF and SWNTs was 94:4:2. Compared with the common process on the market (80:10:10), the energy density of LiFePO4 was effectively improved and the amount of conductive agent added was reduced. Then the SWNTs conductive slurry with LiFePO4 added was placed in a homogenizer, first homogenized at a speed of 800r / min for 30s, and then the speed was automatically increased to 2000r / min for 20min to obtain a uniformly dispersed electrode slurry. Finally, the electrode slurry was evenly coated on a 2*10cm thick 20μm aluminum foil, and a circular electrode with a diameter of 1.2cm was obtained after drying and roller punching. The SEM of the electrode is as follows Figure 3 As shown, it can be seen that SWNTs are evenly wrapped on the surface of the positive electrode particles and connect LiFePO4 particles of different sizes to each other.
[0026] The battery was assembled in a glove box filled with argon and with water and oxygen content less than 0.01 ppm. The order was negative electrode shell, lithium sheet, diaphragm, 50 μL electrolyte, electrode sheet, gasket, shrapnel and positive electrode shell, and then sealed with a pressure of more than 1000 N to obtain a CR2032 button battery. Figure 5 In the first charge and discharge curves of SWNTs and SP at a voltage of 2.5-4.2V, the first discharge specific capacity of SWNTs was 161.53mAh / g, and the first charge and discharge efficiency was 99.27%; in comparison, the first discharge specific capacity of SP was only 149.2mAh / g.
[0027] Figure 6The rate curves at different charge and discharge rates of 0.2C, 0.3C, 0.5C, 1C, 3C, 4C and 0.2C show that even at a high current rate of 4C, there is still a discharge capacity of 103.8mAh / g, while the CNTs have dropped to 0mAh / g at this time.
[0028] Figure 7 The impedance curves of SWNTs and CNTs show that the impedance of the LiFePO4 lithium battery with SWNTs conductive paste is 120mΩ, while that of CNTs reaches 400mΩ, which is more than three times that of SWNTs. This shows that the SWNTs prepared in this patent can effectively reduce the internal resistance of LiFePO4 and improve its conductive performance. Example
[0029] The difference between this embodiment and embodiment 1 is that the temperature of temperature control zone No. 3 is increased to 1050° C., and the final IG / ID value of SWNTs is 7.85. Example
[0030] This embodiment differs from embodiment 1 in that the molar ratio of added ferrocene and sublimed sulfur is 8:1, and the final IG / ID value of SWNTs is 2.71.
[0031] Comparative Example 1 The difference between this comparative example and the embodiment is that the temperature of the high-temperature reaction zone is set to 900° C., and ultimately no SWNTs are generated. The products are mostly multi-walled carbon nanotubes with an IG / ID value of 0.66.
[0032] Comparative Example 2 The difference between this comparative example and the embodiment is that the temperature of the high-temperature reaction zone is set to 950° C., and ultimately no SWNTs are generated. The products are mostly multi-walled carbon nanotubes with an IG / ID value of 0.75.
[0033] Comparative Example 3 The difference between this comparative example and the embodiment is that SP is used as a conductive agent with an addition amount of 2%. The electrochemical performance is finally tested, and the first discharge specific capacity is 149.22 mAh / g, and the first charge and discharge efficiency is 91.74%.
[0034] This study systematically compared existing processes, from both horizontal (temperature) and vertical (ratio) perspectives, and applied them to LiFePO4 cathode materials. The results showed that when the molar ratio of ferrocene to sublimated sulfur was 16:1, the IG / ID value of SWNTs was the highest, indicating the highest degree of graphitization of the single-walled carbon nanotubes at this point. As the proportion of sublimated sulfur increased further, the IG / ID value began to decrease. Furthermore, when the synthesis temperature was 900°C, the prepared carbon nanotubes were multi-walled carbon nanotubes with low crystallinity. Finally, when the SWNTs conductive slurry was applied to LiFePO4 to prepare lithium-ion batteries, testing revealed significant improvements in initial efficiency, high-rate performance, and impedance performance, significantly optimizing the electrical properties of the LiFePO4 cathode material.
[0035] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a single-walled carbon nanotube conductive paste, characterized in that: The following steps are involved: Step 1, weigh a certain amount of ferrocene and sublimed sulfur, mix and grind them evenly in a mortar; Step 2, placing the ferrocene containing sulfur or sulfur-substituted organic matter in step 1 in a preheating area; Step 3: Heat the reaction zone to above 1000°C, and after the temperature stabilizes, heat the preheating zone in step 2 to above 200°C; Step 4: After the temperature stabilizes, a certain amount of methane, hydrogen and inert gas are introduced and the sulfur-containing ferrocene vaporized in step 3 is carried into the high-temperature reaction zone; Step 5: Using chemical vapor deposition to in-situ reduce and catalytically crack to synthesize high-purity and high-conductivity single-walled carbon nanotubes; Step 6: purifying the single-walled carbon nanotubes synthesized in step 5 with hydrochloric acid to remove iron particles in the single-walled carbon nanotubes; Step 7: Weigh a certain amount of the single-walled carbon nanotubes treated in the previous step and mix them with NMP, PVP and PVDF solutions in proportion, and disperse them into a stable and uniform single-walled carbon nanotube conductive slurry through ultrasonic vibration and magnetic stirring.
2. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The molar ratio of ferrocene to sublimed sulfur is 8-32:1, and the sublimed sulfur is a sulfur-containing thio-organic compound.
3. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The preheating zone is required not to be affected by the temperature of the high-temperature reaction zone through equipment modification, that is, when the reaction zone reaches above 1000°C, the temperature of the preheating zone is still below 100°C.
4. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The temperature of the preheating zone is 120-220°C.
5. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The preheating zone and the high-temperature reaction zone must be protected by inert gases Ar2 and N2 throughout the entire process until the reaction is completed and the temperature drops to room temperature.
6. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The flow rate of hydrogen and methane is 1-2:1, and the flow rate of argon, hydrogen and methane is 2:
1. The inert gas and hydrocarbons carry the vaporized sulfur-containing ferrocene. It should be noted that the gas flow rate should not be too large to avoid incomplete reaction between the catalyst and the carbon source and tail end blockage. In situ catalytic cracking requires the simultaneous introduction of a certain amount of hydrocarbons.
7. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The hydrochloric acid purification treatment is to dilute 99.9% concentrated hydrochloric acid to 0.4 mol / L, heat to 80 ° C and stir for 6 hours, then filter and wash until neutral, and repeat 2-3 times.
8. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The addition amount of single-walled carbon nanotubes in the single-walled carbon nanotube conductive slurry is 2-0.5%, PVP:SWNTs=1:5; the maximum power of the ultrasonic power is 650W, the ultrasonic frequency is 40KHz, the ultrasonic oscillation time is 40-90min, the magnetic stirring voltage is 220V / 50Hz, the initial stirring time is 10-15h, the stirring time after the start of ultrasound is 40-90min, and the ultrasound and stirring are alternately cycled 5-8 times.
9. The method for preparing a single-walled carbon nanotube conductive paste according to claim 1, characterized in that: The NMP is N-methylpyrrolidone, and its content is 94-96%.
10. An application of the single-walled carbon nanotube conductive paste according to any one of claims 1 to 9, characterized in that: The prepared single-walled carbon nanotube conductive slurry is suitable for the production of batteries with all positive electrode materials.
Citation Information
Cited By
Single-walled carbon nanotube and preparation method thereof
CN121849920A